RULES AND REGULATIONS OF SHARIAH REPURCHASE AGREEMENT INVESTMENT IN SHARIAH CAPITAL MARKET OF INDONESIA - Ahmad Saparwadi (Journal of Islamic Economics Perspectives, 2023)
The study tries to find out basic principle of regulations related to shariah repurchase agreement investment that can provide legal certainty to the parties and the mechanism of Shariah repurchase agreement transactions. In answering the problems, the research method used is to analyze the positive laws (ius constitum) which are supported by literature studies as a reinforcement of existing regulations. The results of this study are that the legal certainty of Shariah repurchase agreement investment in the capital market can be achieved through the legal substance that has been ratified through regulations, executive, and supervisory in Shariah repurchase agreement activities in the capital market. This investment activity gets legality based on the fatwa of the National Sharia Board-Indonesia Council of Ulama. while the mechanism of Shariah repurchase agreement transactions in the capital market is the same as the transaction of repurchase agreements in general, it's just that what distinguishes it is in terms of actors who must run their companies based on Sharia Principle or has Sharia units, the securities invested based on the sharia principle and the contract used is al-bai' ma'a al-wa'd bi al-syira'. Then there is an Shariah Capital Market Expert as a party or institution that provides an assessment related to the application of Shariah principles by investors in the Indonesian Capital Market.